Easter Attacks In Sri Lanka - Gunasingham, Amresh Lavan (2019)
Several near-simultaneous blasts tore through three churches and three luxury hotels in Sri Lanka on Easter Sunday, the bloodiest outbreak of violence in the South Asian island state since the end of a civil war a decade ago.